Native American Student Healthcare: Health, Hygiene, and Mortality at U.S Off-Reservation Boarding Schools - Estrada, Tatiana (The Toro Historical Review, 2022)
The subject of student health at U.S off-reservation boarding schools is not often discussed in depth in historical research. As such, this study seeks to investigate this topic area and contribute towards bridging that gap. Oftentimes, official records indicated a wide array of efforts undertaken at boarding schools to maintain student health. However, these records conflict with accounts of the practical experience at these schools. Upon examination, the issues experienced at boarding schools stemmed from three interconnected problems: over enrollment, overcrowding, and inadequate funding. These facilities were designed to accommodate a specified student body size, which was exceeded when officials enrolled too many students. As a consequence, resources became stretched thin, and quality of life stagnated at a low point. This affected multiple areas of boarding schools including living arrangements, disease outbreaks, health curriculum, medical care, meal plans, and overall student mortality. Furthermore, these problems were exacerbated by school officials lack of honesty and transparency, with regard to the status of their institutions. When it came time to report to Congress, boarding school representatives frequently glossed over the reality of student health. As a result, it was difficult to get a full understanding of the scope of the problems faced within the boarding school system. Ultimately, school officials placed their institutions above the wellbeing of the students they promised to care for.